Act of April 6, 1936, No. 82, § 8, Ala. Laws 51, 51 - (:unkn) unknown (General Publisher, 1936)
Prohibited committing a crime of violence when armed with a pistol. Individuals armed with a pistol while being unlicensed shall be prima facie evidence of intention to commit said crime of violence.Violators fined not more than five hundred dollars, or imprisoned not more than one year, or both.
--
Keywords: CARRY - INTENT TO COMMIT CRIME